2013
DOI: 10.1002/anie.201308302
|View full text |Cite
|
Sign up to set email alerts
|

High‐Power Electrochemical Energy Storage System Employing Stable Radical Pseudocapacitors

Abstract: The development of electrical energy storage devices that can operate at high charge and discharge rates is fundamentally important, however although electrochemical capacitors (ECs) can charge and discharge at high rates, their electrochemical storage capacity remains an order of magnitude lower than that of conventional lithium-ion batteries. Novel pseudocapasitors are developed, based on the stable persilyl-susbtituted free radicals of the heavy group 14 elements, (tBu2 MeSi)3 E(.) [E=Si (1), Ge (2), and Sn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0
2

Year Published

2014
2014
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 33 publications
2
24
0
2
Order By: Relevance
“…Sekiguchi’s research is centered on low‐coordinate organosilicon compounds, including doubly and triply bonded organosilicon species, and silicon‐centered radicals, cations, anions, and radical ions. He has reported in Angewandte Chemie on anode materials based on persilyl‐substituted free radicals,2a and in Chemistry—A European Journal on isolable aryl‐substituted silyl radicals 2b …”
Section: Awarded …︁mentioning
confidence: 99%
“…Sekiguchi’s research is centered on low‐coordinate organosilicon compounds, including doubly and triply bonded organosilicon species, and silicon‐centered radicals, cations, anions, and radical ions. He has reported in Angewandte Chemie on anode materials based on persilyl‐substituted free radicals,2a and in Chemistry—A European Journal on isolable aryl‐substituted silyl radicals 2b …”
Section: Awarded …︁mentioning
confidence: 99%
“…We have synthesized a series of redox polymers containing nitroxide radical moieties and utilized them as electrode‐active materials in organic radical polymer batteries . Organic batteries are characterized by excellent rate performances and capabilities of fabricating purely organic, flexible, and environmentally benign energy‐storage devices . Radical polymers swell in electrolyte solutions to allow counterions to diffuse smoothly through the polymer layers.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, several other isolable silyl radicals have been reported, including a silyl radical lacking stabilization by π‐conjugation,10a disilene anion11 and cation radicals,12 a disilyne anion radical,13 silylene anion14 and cation radicals,15 alkali‐metal‐substituted silyl radicals,16 and a triplet bis(silyl) radical 17. Moreover, we recently reported that the stable persilyl‐susbtituted Si, Ge, and Sn radicals can work as an electrochemical energy storage system 18. However, isolable and persistent silyl radicals containing other substituents, such as alkyl, aryl, and heteroatom substituents, are less known 6g.…”
Section: Introductionmentioning
confidence: 99%